The phenomenon of school violence in the independent, written press in Algeria ""An analytical study of a sample from the daily newspaper echourouk elyoumi - Daoudi , cherif; bekhouche, nadjib (Journal of Social Sciences and Humanities, 2021)
Through this study, we focused on the journalistic treatment of the phenomenon of school violence in the independent, written press in Algeria. we took in that the daily El Shorouk newspaper as a sample, which in many cases devotes a special page to different educational issues, according to different content on phenomena and practices alien to the education sector and to Algerian society in particular. Through that, we are trying to find out wether the objective of the newspaper is the news or othewise, such as excitement and grooming. The matter that called us to follow up on the topic, to study it, to discuss its problems and to answer the central question: How did Al-Shorouk Al-dailyi approached cases of school violence? . Our study falls within the descriptive studies, with the adoption of a descriptive analytical approach using only the content analysis tool. For that, we chose a sample composed of 12 issues of the daily newspaper Al-Shorouk according to the requirements of the intentinal sample ,so that we analyze it in "quantity and quality" and to extract the general results from our study of this phenomenon, which negatively affects in one way or another the social balance and the normal life.